Surgical field visualization and feasibility of accessory lung lobectomy using a pretied ligature loop via single incision thoracoscopy in canine cadavers - Kim, Chaewon; Lee, Sangjun; Heo, Suyoung (Frontiers in Veterinary Science, 2025)
IntroductionThoracoscopic surgery is a widely accepted minimally invasive technique in veterinary medicine. However, its application in small dogs is limited by the narrow thoracic space, difficulty accessing midline structures, and the requirement for one-lung ventilation. To overcome these limitations, a single-incision subxiphoid approach with low-pressure CO2 insufflation may offer improved visualization and access, but objective, quantitative evidence supporting its feasibility remains insufficient.Materials and methodsEight canine cadavers (6–10 kg) underwent subxiphoid single-port thoracoscopy under mechanical ventilation with non-insufflation and 3 mmHg CO2 insufflation. Visualization quality was quantitatively evaluated using image analysis, and lung lobe accessibility was scored. The feasibility and safety of accessory lung lobectomy using a pretied ligature loop was assessed, including air leakage testing.ResultsCO2 insufflation at 3 mmHg group significantly enhanced thoracoscopic visualization compared to non-insufflation group, particularly by reducing visual obstruction from the left middle and right caudal lung lobes. All lung lobes were accessible through a single incision, though the accessory lung lobe was more difficult to approach (mean exploration score: 0.59). Accessory lung lobectomy using a pretied loop was successfully completed in all cadavers without evidence of air leakage, with an average procedure time of 921 s.DiscussionA single-incision subxiphoid thoracoscopic approach combined with low-pressure CO2 insufflation significantly improves visualization and instrument maneuverability in small-breed canine cadavers. This method also enables complete lung lobe exploration and allows safe and effective accessory lung lobectomy using a pretied ligature loop.